Marine sponges as natural scaffolds : decellularization by supercritical fluid technology and cellularization with osteoblasts for tissue engineering applications - Duarte, Ana Rita C. (2012)
Marine sponges possess remarkable structures, with highly interconnected pores, making them excellent candidates as nature made scaffolds with potential use in tissue engineering strategies. In addition they also exhibit interesting high swelling degree and a skeleton composed mainly of collagen fibres, in some species with embedded siliceous or carbonate spicules. In the present study, several marine sponges (Dysidea avara, Chondrosia remiformis, Axinella damicornis, Petrosia ficiformis, Agelas oroides, Sarcotragus spinosulus, and Psammocinia sp.) were decellularized by supercritical fluids, for further use as natural scaffolds for osteoblasts. Supercritical fluid extraction was performed at 200 bar and 40 °C for 6 hours, in the presence of ethanol (40%), which was used as a co-solvent. The morphology of sponges, namely porosity interconnectivity and mean pore size, was analysed by SEM and micro-CT. To evaluate decellularization, sponges before and after treatment were analysed in sections stained with Hematoxylin- Eosin. Cellularization experiments were performed in S. spinosulus, using Saos-2 cell line. Cells were seeded on the sponge, with further evaluation of cell morphology by SEM, cell viability by Live/dead cell staining together with phalloidin.and cell proliferation by DNA quantification. The results of in vitro tests demonstrate the success of the proposed methodology for the production of natural scaffolds from marine sponges, namely for Sarcotragus spinosulus.